Leadership and Succession in Islam and the Constitution: Finding the Meeting Point between Positive Law and Divine Law - Tiara Rahma Wati; Faiz Musthofa Abbas; Wifaqul Azmi (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
Leadership succession from the perspective of Indonesian Constitutional Law and Islamic Law. In the context of Constitutional Law, leadership succession is regulated in the post-amendment 1945 Constitution, which emphasizes a presidential system of government, direct elections by the people, and term limits for the president. Meanwhile, in Islamic Law, leadership succession does not have a single model but is rooted in the principles of the Qur'an and Sunnah, such as consultation (shura), trustworthiness, justice, and the welfare of the community. This study employs a qualitative method through a literature review approach, analyzing primary and secondary sources. The results of the study show that despite systematic differences between the two, both Constitutional Law and Islamic Law place leadership as a trust that must be carried out with integrity and responsibility to achieve justice and public welfare.